Periacetabular osteotomy: an analysis of social media to determine the most common questions asked by the periacetabular osteotomy population. - Gaddis, John M.; Laboret, Bretton.; Bialaszewski, Ryan.; Bergman, Elizabeth.; LaCross, Jenny.; Mulligan, Edward.; Wells, Joel. (Tufts University. Tisch Library., 2024)
Keywords: Periacetabular Osteotomy, Hip dysplasia, Social media, Questions.; Springer Open.